Framing, Resources and Repertoire of Local Trade Union Action for Health and Safety: A Study Conducted with a Quebec Central Labour Body - Baril-Gingras, Geneviève; Dubois-Ouellet, Sarah (Relations industrielles / Industrial Relations, 2018)
SummaryEmployment and working conditions having an impact on health and safety are some of the most important concerns of workers. Amongst the various means by which trade unions contribute to prevention, the contribution of Worker Safety Representatives (WSR) is well-established and the most studied, including their participation in joint occupational health and safety committees (JOHSC). However, there are surprisingly few studies examining the place of OHS as an issue of workers’ collective action. Conducted with a large Quebec Central Labour Body, this study aims to understand why and how local-level unions concentrate upon these issues, the repertoire of means that they employ and the context that supports or hindus such actions. The conceptual framework is based on previous realistic evaluations of OHS preventive interventions and includes Levesque and Murray’s (2010) trade union power resources and strategic capabilities.In phase I, eleven semi-structured interviews were conducted with union staff members and elected representatives from different sectors, covering a wide array of activities such as unionization, training, negotiation, OHS prevention and compensation. Results also refer to five case studies (phase 2) of local-level trade unions identified by phase 1 respondents as particularly active in relation to prevention.The process by which working conditions having a negative impact on OHS are framed (or not) as trade union issues is examined. Levers and barriers are also identified. Factors affecting the presence of resources for trade union autonomous action aimed at prevention (like the integration of WSR to the union core structure, release time for prevention, etc.) are highlighted. A widely diverse repertoire of workplace-level trade union means of action for OHS is also highlighted by the interviews and case studies, not limited just to those provided by the Quebec OHS regime. It includes the recourse to labour relations mechanisms (e.g. negotiation and strike) and is based on an autonomous agenda, including mobilization. The potential of OHS issues for union revitalization is discussed, as well as the barriers that must be overcome.